THE IMPLEMENTATION OF LITERATURE AND ART EXTRACURRICULARS IN AN ISLAMIC ELEMENTARY SCHOOL - Rahmawati, Fitri Puji; Hazima, Atika Azzahro; Khotimah, Rifaa Husnul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The purpose of the study is to explain the literary and artistic extracurricular program in increasing the interests and talents of students, explain the results of the literature and art extracurricular program, and explain the importance of extracurricular at the elementary school level. The method used in this study is descriptive qualitative. The subjects of this study were 13 students who had an interest in the field of literature and art at MI Muhammadiyah Paseban, Klaten. Data collection techniques are in the form of interviews, observations, questionnaires, field notes, and documentation. Extracurricular literature and art is a vehicle for out-of-school learning that is engaged in developing student achievement in literary and artistic works. The material presented in this extracurricular is training in writing poems and short stories, how to make a biography, and other authorship materials. This extracurricular implementation invites students to directly observe the surrounding environment in making a literary work. This aims to make it easier for students to determine the topic by seeing the object directly. Based on the results of the questionnaire that has been shared, as many as 100% of students stated that they were happy to take part in this extracurricular. The results of interviews with companions show that extracurricular literature and art can improve abilities and encourage students who have potential and interest in literary arts to channel their interests